Efektivitas Vaksin Influenza Berbasis mRNA dalam Meningkatkan Imunitas dan Potensinya Sebagai Pelindung Anak dari Risiko Pneumonia: Analisis - Wijaya, Bryan; Setiawan, Fiona Valencia; Firmansyah, Yohanes (PT Kalbe Farma Tbk., 2025)
Influenza viruses have posed a global threat since the 19th century, presenting serious challenges and threats to public health worldwide. Influenza viruses are among the major seasonal outbreaks impacting health and the economy yearly. Numerous new strains emerge over time due to the antigenic drift of influenza viruses, which undergo mutations. Therefore, vaccines and medical technologies continuously need innovative approaches to stimulate immune responses effectively. mRNA-based influenza vaccines are potentially more effective because of the inclusion of a broader range of antigens that can enhance cellular immunity or expand protection beyond just hemagglutinin (HA) and neuraminidase (NA), they can incorporate more than four antigens (HA) in a single formulation, offering advantages in effectiveness, safety, and rapid large-scale production. mRNA-based influenza vaccines hold significant potential and are expected to benefit children due to their various advantages.